Capacity Building for Puskesmas Health Workers in Compilation of Strategic Plans for Puskesmas Pulo Brayan - Yustina, Ida; Lubis, Ismil Khairi; Aini, Fadilah; Efriandi, Sony (Talenta Publisher, 2023)
The Strategic Plan of the Pulo Brayan Health Center is still not by the standards of Law no. 25 of 2004 concerning the National Development Planning System. The purpose of community service is to increase the capacity of human resources for health workers in preparing the Strategic Plan at the Pulo Brayan Health Center. The activity was attended by 12 health workers from Pulo Brayan Health Center. The methods are in-depth interviews, focus group discussions, and workshops. At the workshop, the speaker provided material and continued with a discussion on the draft strategic plan. The results of the activity are that information and documents needed can be collected, public health problems in the working area of the Puskesmas are identified, problems in the process of preparing the Strategic Plan of the Puskesmas are identified and workshops can be carried out to increase the capacity of participants in formulating strategic plans. Health workers actively participate in discussions at each stage of the implementation of activities and are committed to drafting the Strategic Plan by the knowledge given by the speakers at the workshop.